Impact of SARS-CoV-2 vaccination and of seasonal variations on the innate immune inflammatory response - Jarras, Hend; Blais, Isalie; Goyer, Benjamin; Bazié, Wilfried W.; Rabezanahary, Henintsoa; Thériault, Mathieu; Santerre, Kim; Langlois, Marc-André; Masson, Jean-François; Pelletier, Joelle N.; Brousseau, Nicholas; Boudreau, Denis; et al. (Frontiers in Immunology, 2025)
IntroductionThe innate immune response is an important first checkpoint in the evolution of an infection. Although adaptive immunity is generally considered the immune component that retains antigenic memory, innate immune responses can also be affected by previous stimulations. This study evaluated the impact of vaccination on innate cell activation by TLR7/8 agonist R848, as well as seasonal variations.MethodsTo this end, blood samples from a cohort of 304 food and retail workers from the Quebec City region were collected during three visits at 12-week intervals. Peripheral blood mononuclear cells and polymorphonuclear neutrophils were isolated during the first and third visits and were stimulated with R848 to assess the innate immune response.ResultsOur results show that IL-8 production after stimulation decreased after vaccination. In addition, the IL-8 response was significantly different depending on the season when the visit occurred, for both COVID-19 vaccinated and unvaccinated individuals.DiscussionThis study highlights that innate immune responses can be affected by SARS-CoV-2 vaccination and fluctuate seasonally.